Learning About Disasters Without Reading Risk: A Critique of Geography Education in Junior Secondary Social Studies - Rindi Triantika (Punggawa Legacy Center, 2026)
Disaster education in junior secondary Social Studies has become increasingly important in Indonesia, where schools operate within regions shaped by floods, earthquakes, volcanic activity, landslides, coastal hazards, and climate-related risks. Yet the presence of disaster topics in learning materials does not necessarily mean that students are trained to read risk geographically. This study examines how disaster risk is represented in junior secondary Social Studies materials and whether those representations support spatial risk literacy. A qualitative document-based design was used, supported by critical content analysis. The analysis found that disaster learning is mainly organised around conceptual recognition, general preparedness, and national disaster awareness. Hazard recognition receives clearer treatment than exposure, vulnerability, local capacity, and the spatial relations that explain unequal risk. Maps, images, and public risk information appear in the materials, but they are not consistently used as resources for geographical inquiry. Local space often remains illustrative rather than analytical. The findings suggest that stronger disaster education does not require adding more content, but changing how existing materials work. Definitions, maps, and risk data can support students in connecting classroom knowledge with school surroundings, neighbourhood routines, and local constraints.